Perspectives on early childhood development in China: key dimensions and contextual contributions - Fu, Qianqian; Zhao, Fangfang; Qin, Jinliang (Frontiers in Psychology, 2024)
The recognition of culture and context as pivotal influences on the developmental trajectory of young children has been underscored by numerous developmental theories. Localized knowledge is essential for comprehending cultural universality with specificity for early childhood development (ECD). To explore insights into ECD in China, 13 focus group discussions were conducted with professionals, caregivers, and teachers from four regions. Thematic content analysis was employed to identify patterns and themes, followed by coding to identify more conceptual units of meaning. The findings reveal distinct culture-based skills across four domains of ECD in China, highlighting a local culture that embraces a comprehensive, dynamic, and staged perspective on the development of young children. This study elucidates the multidimensional impact of the environment on young children's development with a focus on children's behavioral characteristics and temperament traits, ECEC practices, and ECEC beliefs that transcend identity, culture, and the economy. This study contributes to the assessment of ECD for future cultural comparisons and enhances the scientific understanding of the interplay between developmental skills in young children and diverse cultural expectations and backgrounds.